El modelo de matrimonio constitucionalmente garantizado por el principio de promoción: El matrimonio igualitario y la nulidad del matrimonio por inobservancia de la forma prescrita para casarse - Plácido Vilcachagua, Alex F. (2014)
Marriage is one of the most important socialand legal institutions of humanity. Over time, its concept has varied and has adapted to thesocial and cultural evolution of our societies.In this article, the author proposes a new constitutional concept of marriage, which includes same-sex couples, explaining also the role that the principle of promotion of marriage, protected in the Constitution, plays in its configuration.